Renin, Aldosterone, and Cortisol in Pregnancy-Induced Hypertension - Lewandowski, Krzysztof C; Tadros-Zins, Monika; Horzelski, Wojciech; Krekora, Michał; Lewinski, Andrzej (Experimental and Clinical Endocrinology & Diabetes, 2023)
Introduction We aimed to assess renin, aldosterone, and cortisol in the early stages of pregnancy-induced hypertension (PIH), i. e., at the time of diagnosis.Methods During the postural test, we measured aldosterone, renin [Liason DiaSorin Inc. (Italy)], as well as cortisol, sodium, potassium, and 24-h urinary sodium and potassium excretion in 62 women with newly diagnosed PIH, 70 healthy women during the 3rd trimester of pregnancy, and in 22 healthy non-pregnant women.Results In all groups, there was a significant increase in aldosterone and renin in upright versus supine posture (p<0.01). Both supine and upright aldosterone concentrations were higher in healthy pregnant women than in women with PIH and the lowest in healthy not-pregnant [supine (median±intequartile range): 25.04±18.4 ng/dL, 18.03±12.58 ng/dL, and 7.48±4.78 ng/dL, p<0.001, upright: 31.60±21.32 ng/dL, 25.11±13.15 ng/dL, and 12.4±12.4 ng/dL, p<0.001, for healthy pregnant, pregnant with PIH, and non-pregnant, respectively]. Supine renin concentrations were higher only in healthy pregnant (p<0.001), while in the upright position, there was a difference only between healthy pregnant and women with PIH (p=0.002). Both in supine and upright positions, there was no difference in the aldosterone-to-renin ratio between healthy pregnant women and women with PIH, though, in both groups, the ratio was higher than in non-pregnant women (p<0.001). Morning cortisol concentrations and 24-h urinary sodium excretion were lower in women with PIH than in healthy pregnant (p<0.001, p=0.002, respectively).Conclusion Hyperaldosteronism is not involved in the etiology of PIH. In PIH, there is also a tendency towards lower sodium excretion and lower morning cortisol concentrations.
Keywords: pregnancy-induced hypertension; gestational hypertension; cortisol; aldosterone-to-renin ratio; SUSPPUP ratio